The Relationship Between Implicit Theories of Intelligence, Achievement Goals and Mathematics Performance Among Jordanian Students - Al-Issa, Riyad Salim Issa (2011)
Dweck’s social cognitive model of motivation offers an explanation of the differences in the way students move toward achievement conditions. According to the model, implicit theories of intelligence are associated with achievement goals and generate unique structure for accounting for and reacting to achievement conditions. Existing data only partially support the social cognitive model proposal that asserts that the influence of implicit theories of intelligence on performance is mediated by achievement goals. The purpose of this study is to determine the associations between implicit theories of intelligence and mathematics performance; and examine the intermediary role of achievement goals between implicit theories of intelligence and mathematics performance using the 2 x 2 framework. An additional question is whether these relationships are unique to Western culture or generally operating across the cultures. The survey method was used in this study. Data were collected from 334 Jordanian high school students who were studying in Amman private schools, Jordan. Results were obtained using correlation and regression analysis. In line with previous research, results indicated significant negative association between implicit theories of intelligence and mathematics performance. All the correlations between achievement goals and mathematics performance were in the predicted direction. However, performance approach goal failed to show significant relation with mathematics performance (r =.07, p> .05). Contrary to predictions, there were positive correlations between entity theory of intelligence and mastery avoidance goal (r =.23, p< .01). The results of multiple mediator analysis were consistent with research hypothesis that implicit theories of intelligence affect the mathematics performance through achievement goals. However,examination of specific indirect effects indicates that among the variables included in this study, only performance avoidance goal is a mediator of the relationship between implicit theories of intelligence and mathematics performance In summary, the results of this study confirm the negative effect of the entity theory of intelligence on mathematics performance;the results confirm the explanation that is suggested by social cognitive model to explain why and how entity theory of intelligence reduces mathematics performance. Results of this study highlight the efficacy of the proposed modification of the social cognitive model of achievement motivation that is based on the 2 x 2 achievement goal framework. Finally, unlike the studies which were conducted in the Eastern cultures, the pattern of results in this study suggests that the achievement goals manifest themself in Arabic culture in a way that is similar to Western culture.